ACCOUNTING IN THE LAW-SCHOOL CURRICULUM. - Graham, Willard J. (The Accounting Review, 1939)
Abstract In the last decade, the point of view and the relative emphasis upon various phase of problems related to accounting practice for lawyers have shifted greatly. In 1930, before the American Law School Association, it was necessary to present evidence that lawyers needed and wanted accounting training. It is no longer necessary to prove that lawyers need some training in accounting. Reason for that depends upon the general relationship between law and accounting and the bounds and limits of the two professions. In spite of the fact that the two professions are fundamentally dissimilar, there are many situations which involve mixed questions of accounting facts and law. Not only do the courts adopt and lend sanction to accounting principles as exemplified in accounting practice; the reverse is equally true-that the law, and administrative bodies created by the law, themselves in turn influence materially the development of accounting principles and practice. The U.S. Securities and Exchange Commission has set forth formally and informally a number of "requirements" for registrants, and is daily rendering "decisions" on disputed points of accounting practice.